Conflict and tension 1918-1939 - Longley, Ellen (Oxford AQA GCSE history, 2016)
Conflict and Tension 1918-1939 is part of a brand new series written specially to match the new 2016 AQA GCSE History specification, and is developed by an expert team led by an experienced head of history and an author with senior examining experience. This Conflict and Tension Wider World Depth Study focuses on the causes of the Second World War, and seeks to show how and why conflict occurred, and why it proved difficult to resolve the issues which caused it. Students will study the complex interests of different states, the role of key individuals and groups in shaping change, and how they were affected by and influenced international relations. Carefully selected Sources allow students the opportunity to analyse and evaluate primary sources in context. Practice Questions and Study Tips help students prepare for the new AQA exam questions, and features such as Extension, Over to you, and How to provide step-by-step explanations of how to put into practice essential history skills such as analysing a source, cartoon or essay writing.